Perspectives for mobile satellite communications in Ka-band (MoSaKa) - Heuberger, Albert; et al. (Proceedings, 4th European Conference on Antennas and Propagation, 2010)
The German geo-stationary Heinrich Hertz satellite mission signalises the growing interest in advanced nomadic and mobile satellite communications at Ka-band frequencies. In the framework of an industrial-academic consortium supported by the German space agency, the project MoSaKa adresses the ground segment required for such missions, in terms of bi-directional reliable non-stationary communication links within a heterogeneous emergency network. Issues like mobile terminal antennas, types of communication links and protocols, as well as a specific measurement testbed are addressed by an interdisciplinary consortium of electronic engineers and computer scientist
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.komele.perspe